Clinical researchEvaluation of left ventricular dyssynchrony using combined pulsed wave and tissue Doppler imaging - Shen, Xuedong; Aronow, Wilbert; Anand, Kishlay; Nair, Chandra K.; Holmberg, Mark J.; Hee, Tom; Maciejewski, Stephanie; Esterbrooks, Dennis J. (Archives of Medical Science, 2010)
Introduction: The combination of pulsed wave (PW) and tissue Doppler imaging (TDI) has been proposed as a new method to assess left ventricular (LV) mechanical dyssynchrony (LVMD), but results have not been validated. We investigated the correlation of a combination of PW and TDI with a positive response to cardiac resynchronization therapy (CRT). Material and methods : We studied 108 consecutive patients who received CRT. Patients with atrial fibrillation were excluded. The time difference (TPW-TDI) between onset of QRS to the end of LV ejection by PW (TPW) and onset of QRS to the end of the systolic wave in LV basal segments with greatest delay by TDI (TTDI) was measured before CRT and during short-term and long-term follow-up. Results : The TPW-TDI interval before CRT was 74 ±48 ms. Intra-observer variabilities for TPW and TTDI were 1.5 ±0.24% and 1 ±0.17%. Inter-observer variabilities for TPW and TTDI were 1 ±0.36% and 1 ±0.64%, respectively. TPW-TDI > 50 ms was defined as the cutoff value for diagnosis of LVMD by receiver operating curve (ROC) analysis. During follow-up of 15 ±11 months, the sensitivity and specificity of TPPW-TDI to predict a positive response to CRT were 98% and 82%, respectively. The area under the ROC curve was 0.92. There was a significant agreement between LVMD determined by TPW-TDI and the positive response to CRT ( = 0.80). Conclusions: Left vertricular dyssynchrony detected by the method combining PW and TDI demonstrated a high reproducibility, sensitivity, specificity and agreement with a positive response to CRT.